Successful laparoscopic management of acute abdominal pain due to spontaneous rupture of subserosal vessels overlying a uterine fibroid: a case report and surgical video - Toshimitsu Maemura; Shigeru Fujita; Noriko Morita; Keiichi Furusawa; Kayo Mitamura; Kenji Nishizawa; Kuniaki Ota (BMC, 2022)
Abstract Background Acute abdomen comprises several emergencies. Hemoperitoneum associated with uterine fibroids, which can present as acute abdominal pain, is rare and difficult to diagnose. Especially, spontaneous hemorrhage from the rupture of the superficial vessels overlying a uterine fibroid is extremely rare, and its diagnosis and management have not been established. Case presentation We report a case of a 55-year-old woman who presented at our hospital with acute abdomen. After performing a computed tomography scan, we conducted a laparoscopic examination and diagnosed hemoperitoneum of ambiguous origin. We treated the patient surgically, performing a laparoscopic myomectomy to remove the origin of the hemorrhage. The patient recovered well. Conclusions We report a case of hemoperitoneum of ambiguous origin that was diagnosed laparoscopically and treated by laparoscopic myomectomy to remove the origin of the hemorrhage. Surgeons should rapidly diagnose and manage acute abdominal pain in women with a history of uterine fibroids to prevent severe morbidity or even mortality. Therefore, laparoscopic surgery is recommended in patients with stable hemodynamics.